The effects of a sensorimotor training and a strength training on postural stabilisation, maximum isometric contraction and jump performance - Bruhn, S.; Kullmann, N.; Gollhofer, A. (International Journal of Sports Medicine, 2004)
Previous studies revealed that adaptations following sensorimotor training, performed to improve functional joint or postural stability, were characterized by improvements in the rate of force development during maximum voluntary isometric contraction. In classical strength training studies using intense loads it has been shown that improvements in rate of force development is mainly due to adaptations in the intramuscular coordination. The purpose of the present study was to compare possible neuromuscular adaptations in two training groups following either sensorimotor or classical strength training over a period of four weeks. Additionally a control group was investigated to contrast the adaptations seen after training. Postural stability, maximum voluntary isometric contraction and performance in squat-jump and in drop-jump were measured before and after training. The results confirmed the positive effects of both training regimen on rate of force development and on maximum strength during maximum voluntary contraction as well as on jump performance, while only the improvements after the strength training were significant. Strength training reduced iMEG, while it was enhanced after sensorimotor training in most testing situations. Strength training had positive effects also on concentric contractions like squat-jump. The sensorimotor training improved performance in reactive drop-jump by enhanced neuromuscular activity immediately after ground contact. It is concluded that classical strength training with high loads basically improves the mechanical efficiency of the efferent drive on the motoneurons, whereas sensorimotor training alters the afferent input on the central nervous system. Both adaptations yield to specific effects during force development.